Managing Student Behavior in Dual Immersion Classrooms: A Study of Class-Wide Function-Related Intervention Teams. (September 2017) - Hansen, Blake D.; Caldarella, Paul; Williams, Leslie; Wills, Howard P.
Classroom management in dual immersion classrooms includes unique challenges. The teacher must instruct and correct in the L2 language, in which students are beginning learners, and effective classroom management strategies appropriate to the L2 context. Class-Wide Function-Related Intervention Teams (CW-FIT) is a positive classroom management program that teaches social skills and uses group contingencies to improve behavior. The present study examined the ability of French immersion teachers to implement CW-FIT in the L2, including the effects of CW-FIT on teacher praise and reprimand rates and as well as on students' classroom behavior. Social validity was also assessed. A single-subject multiple baseline design with embedded reversals was used to evaluate impact in second-, third-, and fourth-grade dual immersion classrooms. Results indicated that dual immersion teachers were able to implement CW-FIT in L2 with fidelity. The intervention significantly increased teacher praise and improved classroom on-task behavior. Changes in teacher reprimand rates were inconsistent. Students and teachers reported CW-FIT to be socially valid.